Influence of machining parameters on fretting fatigue life of Inconel 718. (September 2022) - Infante-García, D.; Díaz-Álvarez, A.; Belda, R.; Díaz-Álvarez, J.; Cantero, J.L.; Giner, E.; Miguélez, M.H.
Graphical abstract: Highlights: Tool wear is the most relevant machining parameter affecting fretting fatigue. Residual stresses proved to be a relevant indicator of fretting fatigue strength. Surface roughness did not significantly affect the fretting fatigue response. Abstract: This work focuses on the analysis of the influence of different machining factors on the fretting fatigue behaviour of Inconel 718. Fretting fatigue tests using a flat-to-flat with rounded edges contact were carried out using specimens with different manufacturing process parameters. The results pointed out the high impact that machining parameters possess in the Inconel 718 fatigue lifetime. Tool wear has shown to be the most significant parameter. Residual stresses measured along the direction of fatigue load have proved to be a relevant indicator of the fretting fatigue behaviour. Lastly, surface roughness has been shown to possess a weaker influence.